English reading comprehension: Difficulty of teaching and some remedial teaching techniques in fourth form at schools Vanga - KUMANZI MUKAKIMBINGI, Cathy (Éducation et développement, 2018)
After several observations, the author of this article has realized that reading understanding of English is not well taught at secondary school. This can be explained by the sub-classification of some English teachers yet qualified. This study used the survey method supported by technical documentation and systematic observation. Data were collected from teachers of English in the fourth year of four schools in the city of Vanga hinterland. After the identification and presentation of the difficulties faced by teachers, researchers propose some techniques to effectively teach the lesson of comprehensive reading in English. Résumé Après plusieurs observations, l’auteur de cet article s’est rendu compte que la lecture compréhensive d’Anglais n’est pas bien enseignée au secondaire. Cette situation peut être expliquée par la sous-qualification de certains enseignants d’anglais pourtant qualifiés. Cette étude a utilisé la méthode d’enquête appuyée par la technique documentaire et l’observation systématique. Les données ont été récoltées auprès des enseignants d’Anglais de quatrième année de quatre écoles de Vanga et de la périphérie. Après l’identification et la présentation des difficultés éprouvées par les enseignants, la chercheuse propose certaines techniques pour bien enseigner la leçon de la lecture compréhensive en Anglais.